Impact of early-life malaria exposure on childhood stunting: A case-control study in high endemic malaria area, Papua, Indonesia - Sahiddin, Muhamad; Ishak, Hasanuddin; Arsin, Andi A.; Pramestiyani, Mustika (Narra J, 2024)
Papua faces public health challenges as a region with high malaria endemicity and a very high prevalence of stunting. Infectious diseases are one of the risk factors for stunting. The aim of this study was to investigate the effect of early-life malaria exposure on stunting among children in Papua. The study was conducted in 14 public health centers (PHCs) in Papua in 2023. Six hundred eighty-one children (227 stunted and 454 non-stunted) were selected using simple random sampling. The study data were gathered from medical records, structured parent interviews, and direct anthropometric measurements of the children. Chi-square tests were performed to determine unadjusted OR, while adjusted OR was calculated using multivariate analysis. The height-for-age z-score was calculated using WHO Anthro version 3.2.2. The results showed that 45.1% of mothers who had malaria during pregnancy had stunted children. The average z-score height-for-age of children from mothers who experienced malaria during pregnancy vs those who did not was -1.69±1.23 vs -1.41±1.55. Among the 84 children who had malaria under one year old, 45.2% experienced stunting. The average z-score height-for-age of children who had malaria under one year old vs those who did not was -1.83±1.24 vs -1.38±1.6. In the unadjusted analysis, malaria during pregnancy (OR 1.74; 95%CI:  1.06–2.87), malaria in children under one year old (OR 1.78; 95%CI: 1.12–2.83), low birth weight status (OR 1.82; 95%CI: 1.08–3.05), family income (OR 1.75; 95%CI: 1.09–2.81), and mother’s ethnicity (OR 1.45; 95%CI: 1.05–2.01) were associated with stunting incidence in children. In the multivariate analysis, mother’s ethnicity (aOR 1.41; 95%CI: 1.00–1.97) and low birth weight status (aOR 1.72; 95%CI: 1.00–2.94) were the only risk factor for stunting. This study suggests a potential association between early-life malaria exposure and stunting in children. In malaria-endemic areas, health interventions targeting malaria prevention during pregnancy and early childhood are necessary to reduce the risk of stunting.